Selective electrochemical recognition of sulfate over phosphate and phosphate over sulfate using polyaza ferrocene macrocyclic receptors in aqueous solution - Beer, P; Cadman, J; Lloris, J; Martinez-Manez, R; Padilla, M; Pardo, T; Smith, D; Soto, J (1999)
Potentiometric and electrochemical studies have been carried out with a family of ferrocene redox-functionalised polyamines (L1-L5) and have been directed towards the discrimination, using electrochemical techniques, between the two oxoanions phosphate and sulfate and the electrochemical sensing of ATP. Potentiometric titrations were carried out in THF-water (70:30 v/v, 0.1 mol dm-3 tetrabutylammonium perchlorate, 25°C) for L1, L2, L3, L5 and in water (0.1 mol dm-3 potassium nitrate, 25°C) for L4. Potentiometric data indicate that all receptors studied form stable complexes with sulfate, phosphate and ATP. Distribution for the ternary diagram system sulfate-phosphate-L2 shows pH dependent selectivity patterns; [L2HjSO4]j - 2 species exist at greater than 90% in the pH range 3-4, whereas the corresponding phosphate complexes are the main species in the neutral and basic pH range. The electrochemical studies are in agreement with the speciation results. Sulfate produces in all cyclic receptors maximum cathodic shifts of the redox potential of the ferrocenyl groups around pH 3-4, whereas maximum cathodic shifts for phosphate were found between pH 7 and 8. This behaviour is not observed for the open-chain tetraamine L5. Selective quantitative electrochemical recognition of sulfate and phosphate in the presence of competing anions in aqueous solution has been achieved using the redox-active polyaza ferrocene macrocyclic L2, L3 and L4 receptors. Additionally ATP is able to cathodically shift the oxidation potential of the ferrocenyl groups of L2 and L3 receptors by up to 100 mV. The electrochemical response of L3 against ADP and AMP is also reported.